2014
DOI: 10.1111/ijd.12544
|View full text |Cite
|
Sign up to set email alerts
|

Safety of performing invasive acne scar treatment and laser hair removal in patients on oral isotretinoin: a retrospective study of 110 patients

Abstract: Isotretinoin does not appear to delay wound healing, and hence invasive procedures can be considered on patients on oral isotretinoin without any compromise on the outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 15 publications
1
41
0
2
Order By: Relevance
“…Laser light penetration is decreased in more darkly pigmented skin. Higher fluences and longer wavelengths are required to produce similar clinical effects in darker skin types but should be administered with care to prevent side‐effects caused by higher absorption of the pigmented epidermis . In darker phototypes we recommend the combined use of chilled contact gel, ice, sapphire chilled tip, cryogen spray delivered by dynamic cooling device or external air cooling to preserve the epidermis and prevent pigmentary complications.…”
Section: Treatment Principlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Laser light penetration is decreased in more darkly pigmented skin. Higher fluences and longer wavelengths are required to produce similar clinical effects in darker skin types but should be administered with care to prevent side‐effects caused by higher absorption of the pigmented epidermis . In darker phototypes we recommend the combined use of chilled contact gel, ice, sapphire chilled tip, cryogen spray delivered by dynamic cooling device or external air cooling to preserve the epidermis and prevent pigmentary complications.…”
Section: Treatment Principlesmentioning
confidence: 99%
“…30,33,34 We recommend against avoidance of laser treatment in patients who are on or have recently stopped using oral isotretinoin (GRADE 2C). [35][36][37]…”
Section: Qualification Of Providers Of Laser And/or Ipl Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Acne scarring can be psychologically detrimental, and withholding potentially effective treatments such as laser resurfacing during and after isotretinoin therapy can negatively impact a patient's quality of life. More recent retrospective cohort studies have challenged this current recommendation and suggested that laser resurfacing (ablative and non‐ablative) may be safe for acne scarring when conducted during and/or within 1–3 months of isotretinoin treatment . However, to the authors’ knowledge there are no randomized split‐face controlled trials that have addressed this issue.…”
Section: Introductionmentioning
confidence: 98%
“…74 Notably, there were no differences between the two groups with regard to adverse outcomes, with no development of keloids, atypical scarring, or delayed wound healing following laser therapy. No complications were seen in 35 patients taking isotretinoin 10 mg/kg daily for at least one month prior to a mean of 3.1 sessions with 1,550 nm erbium-doped fiber laser therapy.…”
mentioning
confidence: 88%